2020
DOI: 10.1093/ntr/ntaa104
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Impact of Health Warnings and Plain Tobacco Packaging in Seven Latin American Countries: Results of a Simulation Model

Abstract: Introduction The burden of disease attributable to tobacco use in Latin America is very high. Our objective was to evaluate the 10-year potential impact of current legislation related to cigarette packaging and warnings and expected effects of moving to a higher level of strategies implementing cigarette plain packaging on health and cost outcomes in Argentina, Bolivia, Brazil, Chile, Colombia, Mexico, and Peru, using a microsimulation model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…This was consistent with earlier estimates in the US 3 and other countries. 26 The reductions in overall estimated smoking prevalence were similar to those reported in Levy et al 3 : 10% (range, 4%-19%). However, this study's model estimated fewer smoking-attributable deaths averted during a longer period owing to the model's projections of lower smoking prevalence in the baseline scenario compared with the projections of Levy et al 3 Recent studies have found that smoking rates among US youths and young adults have decreased at especially fast rates 4,5 ; thus, the outcomes of future policy changes will be attenuated by these underlying trends at baseline.…”
Section: Discussionsupporting
confidence: 86%
“…This was consistent with earlier estimates in the US 3 and other countries. 26 The reductions in overall estimated smoking prevalence were similar to those reported in Levy et al 3 : 10% (range, 4%-19%). However, this study's model estimated fewer smoking-attributable deaths averted during a longer period owing to the model's projections of lower smoking prevalence in the baseline scenario compared with the projections of Levy et al 3 Recent studies have found that smoking rates among US youths and young adults have decreased at especially fast rates 4,5 ; thus, the outcomes of future policy changes will be attenuated by these underlying trends at baseline.…”
Section: Discussionsupporting
confidence: 86%
“…In Argentina, there are 9 million smokers (over a total population of 45 million inhabitants) and tobacco consumption causes 45 000 deaths per year. 34 Since 2011, tobacco prevalence has diminished. According to the latest National Survey of Risk Factors, in 2018 the prevalence of cigarette consumption in the adult population was 22.2%, 7.5 percentage points below the prevalence registered in 2005.…”
Section: Datamentioning
confidence: 99%
“…To our knowledge, this is the first experiment in Colombia testing the effects of standardised packaging and larger health warnings with these innovative methodologies (i.e., eye‐tracking and DCE) and our research supports and replicates previous work conducted elsewhere [ 7 , 8 , 10 , 12 , 20 , 27 ]. The implementation of these policies might contribute to reducing the burden that tobacco places on the Colombian economy and health care system [ 41 ]. Although governments may require, or at least welcome, ‘local’ evidence on the effects of tobacco control policies, such as larger health warnings and standardised packaging (as per the Colombian Ministry of Health) [ 1 ], our research demonstrates that these policies are likely to have similar effects cross‐culturally.…”
Section: Discussionmentioning
confidence: 99%